Immunotherapies in Rasmussen's Encephalitis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
Corticosteroids, IV immunoglobulins (IVIg), cyclophosphamide, therapeutic plasma exchange (TPE), and protein A IgG immunoadsorption (PAI) were evaluated in 15 patients with confirmed Rasmussen's encephalitis (RE) and reported from various centers in Italy.